Estudio de factibilidad para la creación de una empresa productora y comercializadora de manteca de cacao cantón Quevedo, año 2014 - Vélez Segovia, Lisseth Elizabeth (2015)
This research was conducted in the city of Quevedo, the same that is located in the central area of the country to 74 meters above sea level with an area of approximately 302.8 km2, its geographical position, is confluence of major roads of the national network. The problem investigated; It is based on diagnosing how the influence the feasibility study for the creation of a producer and marketer of cocoa butter company in Canton Quevedo, formulating objectives and identify the supply and demand for the creation of a producer and marketer of butter cocoa, determine the technical commercial studio project for creating a manufacturer and marketer of cocoa butter and ensure the financial economic study to test the profitability of the project. To comply with the objectives of the investigation, it was necessary to use methods: inductive, deductive, analytical, together with the types of research: field in which the primary information (scene) was obtained bibliographic allowed investigate and review the literature related to research; this applied to the design of the surveys was made on a sample of 395 people including cocoa producers Quevedo Canton, and an interview with the manager of the La Pepa de Oro Vinces canton...........